Developing feed business with farmer groups in Farakala and Baroueli, Mali: Monitoring the use of two delivered feed processing units - Rudiger, Udo; Sacko, Idrissa (International Livestock Research Institute (ILRI), 2024)
As part of the Innovation Package No. 2, "Gender-Sensitive Integrated Livestock Health Packages through Behavior Change Communication (BCC)," the initiative aims to enhance the quality, quantity, and availability of feed for small ruminants, benefiting both male and female farmers. It focuses on improving feed production efficiency, feeding strategies, and cost savings to raise investment capacity and generate additional income through affordable small-scale mechanization. Key activities include identifying suitable machinery, developing context-specific feed formulas, strengthening cooperatives, and providing knowledge on marketing and financial management.